Tingkat Pengetahuan Pemirsa pada Isi Pesan Iklan Layanan Masyarakat TBC di Televisi - -, Juwito (Universitas Brawijaya, Indonesia, 2009)
The purpose of this research is to know level of knowledge society in Surabaya concerning content order society service advertisement about TBC in television. The variable of this Research is knowledge level by using scale of ordinal as measurement scale. This Research population is society of Surabaya beholder of television, while sample taken with method of multistage sampling random cluster. its Method data collecting to quesioner and to know level knowledge of participant used by frequency distribution. Result of this research indicate that level knowledge of society most residing in category indicating that basically society have owned knowledge which pathological enough Tuberkulosis (TBC). after seeing society service advertisement in television knowledge of responder become more understanding and comprehending is pathological of Tuberkulosis, cause and how curing it. Conclusion and suggestion able to be taken away from this research is that level knowledge of society most residing at high category which indicate that because education level had by society of Surabaya assessed high enough so that can analyse various given information in around disease of Tuberkulosis (TBC), besides all the responder have owned good awareness about is important [of] him keep in good health ownself and also all family. Mount knowledge which is â€œ highâ€ indicating that basically society of Surabaya have owned knowledge which many is pathological of Tuberkulosis from various source of like when there is counselling performed by on duty local health. Keywords: Knowledge, society, service advertisement, TBC